Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days
8104911739
For Business Enquiry

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

Prove

Asked by 27th August 2008, 9:01 PM
Answered by Expert
Answer:

 2cosa cosb cos(a+b) = 2 cosa cosb(cosacosb - sinasinb)

=2cos2a cos2b - 2cosa cosb sina sinb

= cos2a cos2b +cos2a cos2b - 2cosa cosb sina sinb

=(1-sin2a)cos2b + (1-sin2b) cos2a - 2cosa cosb sina sinb

now L.H.S. will be

=cos2a + cos2b -(1-sin2a)cos2b - (1-sin2b) cos2a + 2cosa cosb sina sinb

=sin2a cos2b +sin2b cos2a + 2cosa cosb sina sinb

=(sina cosb+cosa+sinb)2 = sin2(a+b)

Answered by Expert 8th September 2008, 6:00 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp